Periodic courses of human 1-34 parathyroid peptide alternating with calcitriol paradoxically reduce bone remodelling in spinal osteoporosis. - Reeve, J; Arlot, M; Price, T; Edouard, C; Hesp, R; Hulme, P; Ashby, J; Zanelli, J; Green, JR; Tellez, M (1987)
In an attempt to achieve an anabolic response in both axial and peripheral bone, we treated twelve patients with osteoporosis using human 1-34 parathyroid peptide given discontinuously. The peptide was given as seven daily subcutaneous injections followed by 21 days' treatment with 0.25 mg calcitriol orally. This regime was repeated cyclically for at least sixteen cycles, of which the first four were at a lower dose of hPTH 1-34 than used subsequently. The results of treatment were monitored by kinetic, densitometric, histomorphometric and biochemical studies performed before and during treatment. Two patients developed hPTH 1-34 binding in their plasma during treatment: this was presumed to be due to the development of antibodies. The remainder, instead of increasing their indices of bone turnover as judged by iliac bone histomorphometry, were found to have consistent reductions in trabecular resorption surfaces. The other indices of bone formation and resorption measured showed no change or comparable reductions. The small increases seen in total body calcium were consistent with 'in-filling' of deleted basic multicellular units (BMUs). Because there is no evidence that calcitriol alone causes comparable reductions in activation of bone remodelling in osteoporosis, interruption of treatment with hPTH 1-34 after 7 days may have led to a failure of the activation mechanism to proceed to the resorption stage, with a consequent overall reduction in remodelling activity. This type of treatment regime, with its calcitonin-like effect, might be effective in reducing net bone loss due to imbalance between bone formation and resorption at the BMU level, particularly in patients with increased numbers of BMUs ('high turnover' osteoporosis).(ABSTRACT TRUNCATED AT 250 WORDS)